MacBeth as a MCDA Tool to Benchmark the Iberian Airports - José Braz; Emilia Baltazar; Jorge Silva; Margarida Vaz (European Regional Science Association (ERSA), 2011)
This work relates to airports benchmarking which is a very important issue for stakeholders. Airports benchmarking depends on airport performance indicators which are also important issues for business and operational management, regulatory bodies, airlines and passengers. There are several sets of indicators to evaluate airports performance and also there are several techniques to benchmark airports. This work uses MacBeth - a MCDA (Multi-Criteria Decision Analysis) tool, to evaluate the attractiveness of the most important Iberian Airports. This approach is a new one and the preliminary results are very promising when compared with some traditional studies of airports benchmarking.
Keywords: 330; Airports Benchmarking; MCDA/MacBeth; Iberian Airports